Press Communication Strategies in Twitter. A Comparison between Spain and Portugal - Belén Puebla Martínez; Flávia Gomes-Franco e Silva (Disertaciones, 2015)
The development of the Web 2.0 has caused the appearance of several Social Media, whose dynamics leads to a continuous exchange of content by users. The consolidation of the current communication model, characterized by the horizontality, bidirectionality, and decentralization, is one of the most prominent effcts of the interactivity in the process of building the information scene. Thereby, traditional media must face the challenges involved in adapting the traditional journalism to the audience participation in content production and new ways of broadcasting. This study proposes an analysis of the communication strategies used by cybermedia on Twitter microblogging, emphasizing the adequacy of journalistic messages to the typical narrative of this digital environment. In order to make a comparison between Spain and Portugal, we have analyzed the profiles of the newspapers with the largest circulation in their countries of origin: El País (Spain) and Jornal de Notícias Portugal). The study reveals both the underutilization of Twitter’s conversational potential by both newspapers and the imminent need to set out style rules about the use of resources such as mentions or hashtags.